Reconstruction of the binding pathway of an anti-HIV drug, Indinavir, in complex with the HTLV-1 protease using unaggregated unbiased molecular dynamics simulation. (February 2022) - Sohraby, Farzin; Aryapour, Hassan
Abstract: Retroviruses are a growing concern for the health of human beings, and one of the dangerous members of this family is the Human T-cell Leukemia Virus 1 (HTLV-1) virus. It has affected more than 20 million people so far, and since there are no registered treatments against it yet, urgent treatment solutions are needed. One of the most promising drug targets to fight this virus is the protease enzyme of the virus's protein machinery. In this study, by utilizing a computational method called Unaggregated Unbiased Molecular Dynamics (UUMD), we reconstructed the binding pathway of a HTLV-1 protease inhibitor, Indinavir, to find the details of the binding pathway, the influential residues, and also the stable states of the binding pathway. We achieved the native conformation of the inhibitor in 6 rounds, 360 replicas by performing over 4 micro-seconds of UMD simulations. We found 3 Intermediate states between the solvated state and the native conformation state in the binding pathway. We also discovered that aromatic residues such as Trp98 and Trp98′, catalytic residues Asp32 and Asp32′, and the flap region's residues have the most influential roles in the binding pathway and also have the most contribution to the total interaction energies. We believe that the details found in this study would be a great guide for developing new treatment solutions against the HTLV-1 virus by inhibiting the HTLV-1 protease. Graphical Abstract: ga1 Highlights: The HTLV-1 protease is a potent protein target for fighting the HTLV-1 virus. Unraveling the binding pathway of an anti-HIV drug, Indinavir, to the HTLV-1 protease by Unaggregated Unbiased Molecular Dynamics simulation method. Understanding the role of different regions of the HTLV-1 protease such as the Flap regions, and the aromatic residues such as Trp98 and Phe67 in the binding pathway.